2022
DOI: 10.3389/falgy.2022.859126
|View full text |Cite
|
Sign up to set email alerts
|

Linear Epitope Binding Patterns of Grass Pollen-Specific Antibodies in Allergy and in Response to Allergen-Specific Immunotherapy

Abstract: Allergic diseases affect many individuals world-wide and are dependent on the interaction between allergens and antibodies of the IgE isotype. Allergen-specific immunotherapy (AIT) can alter the development of the disease, e.g., through induction of allergen-specific IgG that block allergen-IgE interactions. The knowledge of epitopes recognized by allergy-causing and protective antibodies are limited. Therefore, we developed an allergome-wide peptide microarray, aiming to track linear epitope binding patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Their anti-β-parvalbumin antibody repertoires were largely established at the time of sampling and little evolution was observed over time, although with some fluctuations. Past studies of immune responses to peptide-defined epitopes of aeroallergens (grass allergens and PR-10-type allergens like Bet v 1) in the same cohort in response to vaccination identified an early establishment of a dominant, individualized epitope reactivity profile that remained relatively stable throughout the final years of the study ( 20 , 21 ). The epitope recognition of pre-existing aeroallergen-specific humoral immunity similarly remained stable over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their anti-β-parvalbumin antibody repertoires were largely established at the time of sampling and little evolution was observed over time, although with some fluctuations. Past studies of immune responses to peptide-defined epitopes of aeroallergens (grass allergens and PR-10-type allergens like Bet v 1) in the same cohort in response to vaccination identified an early establishment of a dominant, individualized epitope reactivity profile that remained relatively stable throughout the final years of the study ( 20 , 21 ). The epitope recognition of pre-existing aeroallergen-specific humoral immunity similarly remained stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that allergen-specific B cell clones expanded early during a response and remained dominant over time. Epitopes recognized by aeroallergen-specific IgE were commonly also recognised by the IgG population of the same subject ( 20 , 21 ), suggesting that there might be a clonal relationship between dominant antibodies over time. Sequencing of antibody-encoding genes, several of which encoded antibodies with defined aeroallergen specificity of these allergic subjects, demonstrated that IgE-encoding allergen-specific clones not uncommonly were maintained during an extended period of time, even throughout the entire 3-year study period ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the identification of patterns in epitopes provides valuable insights for designing therapies and vaccines based on the antibody–antigen interaction, for example, using high-throughput data from epitope libraries to train ML algorithms to better predict epitopes involved in specific antibody–antigen interactions. Consequently, better strategies can be employed to neutralize pathogens and boost the humoral and immune response. , In the diagnostics field, the COVID-19 pandemic has shown that the rapid development of reliable antibody/antigen detecting devices is paramount for the early detection and control of new infectious pathogens. The fast production of such devices can help in evaluating the exposure to pathogens and levels of immunization after treatments or vaccination.…”
Section: Discussionmentioning
confidence: 99%